Fenton-Like Reaction between Copper Ions and Hydrogen Peroxide for High Removal Rate of Tungsten in Chemical Mechanical Planarization. (14th February 2018) - Kim, Kijung; Lee, Kangchun; So, Sounghyun; Cho, Sungwook; Lee, Myeongjae; You, Keungtae; Moon, Jinok; Song, Taeseup
Abstract : The Fenton reaction has been used for the tungsten oxidation under acidic conditions in tungsten chemical mechanical planarization (CMP). However, the narrow working pH window required for ideal reaction limits its application. Herein, we report a simple Fenton-like system via the reaction between copper ion and hydrogen peroxide (H2 O2 ) for the tungsten oxidation over a broad pH range. Copper ion was employed as a reactant with H2 O2 for the Fenton-like reaction, resulting in high production rates of hydroxyl radicals in the range of acidic to neutral pH, which leads to a high rate of tungsten oxidation. As a result, the Fenton-like reaction between copper ions and H2 O2 enables the high removal rates of tungsten films during CMP process in acidic to neutral pH ranges.